The Relations between Burden and Resourcefullness with Life Quality of Severe Mental Illness Caregiver - Debby Sinthania; Zabidah Putit; Dewi Eka Putri (Elevate, 2018)
Background: The patient of severe mental illness can not running their daily life independently, they have limitation in activity, having disorder behavior and needs help in almost every activity of their life, so they need caregiver. Caregiver needs to balancing between work, family and nursing the patient, till they abandon themselves and having stress, anxiety and also pressure which affected to their life by reducing their life quality. The reducing of life quality of the caregiver is affected by several factor like burden and resourcefulness. Purpose: To see the relation between burden and resourcefulness with life quality of the caregiver. Method: This research is correlative analytic with 184 caregiver as respondent. Using Accidental Sampling Technique. This research was conducted on March to October 2015. The data collecting was taken by using questioner. Results: The result of this research shows that there is a meaningful relation between burden and resourcefulness with life quality of severe mental illness caregiver (p<0.05), and the most dominant factor that affected their life quality is their education level. Conclusion: The result of this research is expected to be an input for the caregiver and the institution on behalf to maintain the life quality of the caregiver and also give the caregiver education about health in a form of psychoeducation, conseling, improving group support, family support, and spiritual support for improving the life quality of caregiver.